A rapid enzyme-catalyzed pretreatment of the acidic oil of macauba (Acrocomia aculeata) for chemoenzymatic biodiesel production. (February 2017) - Teixeira, Danielle Altomari; da Motta, César Rezende; Ribeiro, Claudia Maria Soares; de Castro, Aline Machado
Graphical abstract: Highlights: Acrocomia aculeata is a promising feedstock for biodiesel production. Lipozyme 435 (5% w/w) reduced 91.5% of macauba oil acidity in 4 h. Enzyme was robust at a broad temperature range (20–45 °C). Concomitant esterification and transesterification was observed. Abstract: Macauba ( Acrocomia aculeata ) is a plant with high potential of oil supply for biodiesel production. However, the high acidity (35–43%) of this oil disqualifies it from use in industrial biodiesel production plants that use alkaline transesterification as the synthesis reaction. Thus, technologies such as the use of biocatalysts to reduce oil acidity are necessary to better monetize the carbon present in that biomass. In the present study, a commercial lipase (Lipozyme 435) was used for the esterification of free fatty acids (FFAs) in the oil to reduce the acidity. Lipozyme 435 performed well under broad temperature (20–45 °C) and water content (560–30000 ppm) ranges, and its performance was maximized in a substrate (methanol:FFA) molar ratio of 2. The lowest final FFA content achieved was 1.09%, corresponding to a global conversion rate of 97.22%. The fatty acid methyl esters content in the treated oil (55%), determined by 13 C NMR, indicated that Lipozyme 435 can also catalyze the transesterification of the glycerides in the oil. The versatility under different operational conditions and stability over long use (up to 150 times) indicated that Lipozyme 435 is a very suitable biocatalyst for the proposed process, contributing to a better economic attractive option.